1998
DOI: 10.2307/2999576
|View full text |Cite
|
Sign up to set email alerts
|

The Method of Simulated Scores for the Estimation of LDV Models

Abstract: Econometrica publishes original articles in all branches of economics-theoretical and empirical, abstract and applied, providing wide-ranging coverage across the subject area. It promotes studies that aim at the unification of the theoretical-quantitative and the empirical-quantitative approach to economic problems and that are penetrated by constructive and rigorous thinking. It explores a unique range of topics each year-from the frontier of theoretical developments in many new and important areas, to resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
158
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(161 citation statements)
references
References 22 publications
1
158
0
2
Order By: Relevance
“…When exact probabilities are used, the method of scores is the same as maximum likelihood, since the log-likelihood function is maximized when the average score is zero. Hajivassiliou and McFadden (1998) suggested using simulated scores instead of the exact ones. They showed that, depending on how the scores are simulated, MSS can differ from MSL and, importantly, can attain consistency and efficiency under more relaxed conditions.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…When exact probabilities are used, the method of scores is the same as maximum likelihood, since the log-likelihood function is maximized when the average score is zero. Hajivassiliou and McFadden (1998) suggested using simulated scores instead of the exact ones. They showed that, depending on how the scores are simulated, MSS can differ from MSL and, importantly, can attain consistency and efficiency under more relaxed conditions.…”
Section: Motivationmentioning
confidence: 99%
“…The most widely used probit simulator is called GHK, after Geweke (1989Geweke ( , 1991, Hajivassiliou (as reported in Hajivassiliou and McFadden, 1998), and Keane (1990Keane ( , 1994, who developed the procedure. In a comparison of numerous probit simulators, Hajivassiliou et al (1996) found GHK to be the most accurate in the settings that they examined.…”
Section: Ghk Simulatormentioning
confidence: 99%
“…The probit simulators draw from a (J!1)-dimensional distribution of utility differences, while the mixed logit simulator draws from a mixing distribution whose dimension is determined by the specification of the model. Hajivassiliou et al (1992) found the GHK simulator (due to Geweke, 1991;Hajivassiliou and McFadden, 1990;Keane, 1990) performed better than other probit simulators for the specifications that they examined. To our knowledge, there has been no comparison of probit simulators with the simulator for mixed logit with normal .…”
Section: Pure Probits: Normal and Standard Normal Formentioning
confidence: 99%
“…It can be evaluated numerically through simulation techniques. We employ the Maximum Simulated Likelihood Method using the GHK simulator (Geweke 1989, Hajivassiliou and McFadden 1998, and Keane 1994; see also Train 2009) that is implemented in the user-written command cmp in Stata to estimate the multivariate probit model (see Roodman 2009). Table 12 in the Appendix depicts the differences in marginal effects between the single probit and the 7-equation multivariate probit estimates for our two main variables of interest.…”
Section: Resultsmentioning
confidence: 99%